1979
DOI: 10.1172/jci109564
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Fate of Chylomicron Phospholipids and Apoproteins in the Rat

Abstract: A B S T R A C T To study the metabolic fate of chylomicron phospholipid and apoproteins, 15 mg of doubly labeled ([3H]leu, [32P]phospholipid) rat mesenteric lymph chylomicrons were injected as an intravenous bolus into conscious rats. The specific radioactivity, composition, pool size, and morphology of the plasma lipoproteins were determined after 2-60 min. After injection of chylomicrons, there was a rapid transfer of radioactivity into high density lipoproteins (HDL). At peak specific activity in HDL (2-5 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0
2

Year Published

1984
1984
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(62 citation statements)
references
References 49 publications
2
58
0
2
Order By: Relevance
“…Plasma apoA-I levels in healthy humans increases after ingestion of a fatty meal (35). Moreover, apoA-I can be transferred from chylomicrons to HDL (36). Thus, in our Lpcat3 KO mice, the observed significant reduction in plasma apoA-I level is the major outcome of defective absorption of cholesterol, triglycerides, and phospholipids (Fig.…”
Section: Discussionmentioning
confidence: 71%
“…Plasma apoA-I levels in healthy humans increases after ingestion of a fatty meal (35). Moreover, apoA-I can be transferred from chylomicrons to HDL (36). Thus, in our Lpcat3 KO mice, the observed significant reduction in plasma apoA-I level is the major outcome of defective absorption of cholesterol, triglycerides, and phospholipids (Fig.…”
Section: Discussionmentioning
confidence: 71%
“…3940 However, Forte et al 41 have shown that heparin-induced lipolysis of plasma from HTG subjects results in the accumulation (at d= 1.006 to 1.063 g/mL) of flattened, liposomelike vesicles and large spherical particles with lamellar structure on the surface. Tall et al 40 have shown that in vivo lipolysis of TG-rich lipoproteins in rats after an ir jection of a large dose of chylomicrons results in the appearance of liposome-like vesicles in blood. These in vivo data suggest that free lipolytic surface remnants and/or surface remnant-enriched remnants of TG-rich lipoproteins may exist under certain circumstances in circulating blood, eg, in dyslipidemic subjects or during the postprandial lipemic state.…”
Section: Discussionmentioning
confidence: 99%
“…During the metabolism of chylomicron TG by LPL, most of the polar lipids are released as vesicular structures (156)(157)(158) and are transferred to HDL by the action of PLTP (159,160), where PE and PC are metabolized by the action of hepatic lipase and LCAT, which do not metabolize SM (161). LPL may also act on glycerophospholipids in chylomicrons (162).…”
Section: Chylomicron and Vldl Smmentioning
confidence: 99%